A method for preparing high entropy alloy using cascade electrical exchange technology
Through cascaded electrical exchange technology, multiple cations are introduced into the solution in sequence, which solves the problem of difficulty in synthesizing multi-component nanoparticles in the prior art, and realizes the efficient preparation of multi-component high-entropy alloys, improving the composition complexity and production efficiency of nanoparticles.
Patent Information
- Application Number
- CN202411897034.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The prior art is difficult to efficiently synthesize nanoparticles composed of multiple elements directly by solution method, especially elements containing large chemical properties, and cation exchange reactions limit the versatility of composition design.
Using cascaded electrical exchange technology, up to 6 cations are introduced into metal oxide particles in sequence, and the introduction of cations is controlled sequentially by controlling the cations in the aqueous solution to achieve the preparation of multi-component high-entropy alloys.
A way to rationally design and synthesis of multi-component metal oxides has been opened up, and the efficient preparation of multi-component high-entropy alloys has been achieved, which has improved the production efficiency of nanoparticle composition complexity.
Smart Images

Figure CN119372734B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemical deposition and relates to a method for preparing a high entropy alloy by utilizing a cascade electrical exchange technology. Background Art
[0002] In recent years, the composition of nanoparticles plays a key role in determining their properties. In order to meet the demanding requirements in catalysis, optoelectronic devices, sensing and biomedical fields, it is often necessary to increase the compositional complexity of nanoparticles. There are currently a variety of methods to prepare nanoparticles composed of multiple materials, including templates, surface patterning, local deposition and nanoreactor technologies. However, these methods can only produce products in very low yields (microgram levels) and require specialized equipment. Solution methods can prepare large quantities of nanoparticles using benchtop chemical reagents and ordinary laboratory glassware. However, it is very challenging to directly synthesize nanoparticles composed of multiple elements using solution methods, especially those that need to include elements with large chemical properties. For example, it is difficult to make heterostructured nanoparticles composed of only two materials.
[0003] Schaak et al. introduced new cations into nanoparticles one by one through partial cation exchange reactions, thus forming extremely complex nanoparticles in composition and interface. Cation exchange reactions follow certain mobility, solvation energy and Lewis acid-base interactions, so the cation exchange process limits the versatility of composition design. Exploring new mechanisms driving the exchange between different cations is of great significance for the design of multi-component nanoparticles. Zinc displacement reactions usually occur between active metal nanoparticles and noble metal ions driven by redox potential differences, usually producing core, shell or hollow metal nanoparticles.
[0004] In 2013, Hyeon et al. first discovered the interaction between Mn3O4 or Co3O4 nanocrystals (~ 20 nm) and Fe 2+ or Sn 2+ Electroexchange reactions between ions. Here, a cascade electroexchange method is developed to rationally incorporate cations into metal oxide microparticles in a sequential manner. Up to 6 cations are introduced into the microparticles (~ 10µm) in sequence according to their redox potential in aqueous solution at room temperature. Cations that are already at the highest valence can also be added by activating the microparticles with reducing or intermediate valence ions. The introduction of cations into the structure according to simple criteria based on the redox potential of the different cations opens up a path to the rational design and synthesis of multicomponent metal oxides. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a high entropy alloy by using cascade electrical exchange technology in view of the shortcomings of the prior art.
[0006] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is specifically as follows: as a first aspect, the present invention provides a method for preparing a high entropy alloy using a cascade electrical exchange technology, comprising the following steps: using a (Ag7O8)X superstructure material as a template, sequentially undergoing ion exchange reactions with a variety of metal salt solutions; in each ion exchange reaction, detecting the progress of the ion exchange reaction by an open circuit voltage, separating the reactants before the open circuit voltage value stabilizes, and preparing a multi-component high entropy alloy hollow superstructure material;
[0007] The oxidation potential of the metal cations in the plurality of metal salt solutions is lower than the oxidation potential of the silver ions in the (Ag7O8)X superstructure material, and the oxidation potential gradually decreases in the order in which the (Ag7O8)X superstructure material is introduced; the X anion is selected from NO3 - , HSO4 - , ClO4 - , F - , BF4 - One or more of .
[0008] Furthermore, the concentration of the metal salt solution is greater than 50 mmol / L.
[0009] Furthermore, the (Ag7O8)X superstructure material is prepared by the following method: a three-electrode system is used, a deionized water solution containing a silver ion compound and H3BO3 is used as an electrolyte, and a step-by-step decreasing voltage mode or a multiple step-by-step decreasing voltage mode is used to electrodeposit the (Ag7O8)X superstructure material on a working electrode; wherein the voltage of the electrodeposition is greater than or equal to 1.5 V, and the silver ion compound is one or more of AgNO3, Ag2SO4, AgClO4, AgF, and AgBF4.
[0010] Furthermore, the (Ag7O8)X superstructure material is used as a template to sequentially undergo ion exchange reactions with a variety of metal salt solutions, specifically: the (Ag7O8)X superstructure material is used as a conductive electrode (as a positive electrode), the metal cation solution is used as an electrolyte (as a negative electrode), and the carbon rod is used as a counter electrode; high-valent silver ions gradually diffuse from the (Ag7O8)X superstructure material from the inside to the outside, and the metal cations gradually adhere to the surface of the (Ag7O8)X superstructure material to form a growing AgYO2 shell (Y represents the metal element in the metal cation, such as Ni, Co, etc.), thereby obtaining the second-generation hollow metal oxide material AgYO2, and the crystallographic similarity between orthorhombic Ag7O8 nitrate and trigonal AgYO2 reduces the lattice distortion between the Ag7O8NO3 and AgYO2 core-shell; the second-generation hollow metal oxide material AgYO2 is used as a template, and the above steps are repeated to react with metal cations with an oxidation potential lower than Y to obtain multi-generation and multi-component high-entropy alloy hollow superstructure materials.
[0011] Furthermore, it also includes: introducing the highest valence cation into the (Ag7O8)X superstructure material or the nth generation multi-component high entropy alloy hollow superstructure material, specifically, placing an intermediate valence cation solution in a first container, inserting a carbon rod, placing the highest valence cation solution to be introduced in a second container, inserting a gold electrode covered by the (Ag7O8)X superstructure material or the nth generation multi-component high entropy alloy hollow superstructure material, connecting the gold electrode to the carbon rod with a copper wire, connecting the first container and the second container with a liquid bridge, and setting an ion exchange membrane on the liquid bridge to allow only X anions to pass through; wherein the oxidation potential of the intermediate valence cation is higher than that of the highest valence cation.
[0012] As a second aspect, the present invention provides a multi-component hollow superstructure material prepared by the method described above.
[0013] As a third aspect, the present invention provides a use of the multi-component hollow superstructure material in preparing microcapsules, using Co 2+ and Fe 2+ A metal salt solution is prepared to obtain Ag(Co, Fe)O2 magnetic superstructure material, and the microcapsule is used to deliver drugs to target locations in the human body.
[0014] As a fourth aspect, the present invention provides a use of the multi-component hollow superstructure material in preparing a SERS substrate.
[0015] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0016] (1) The present invention opens up a path for the rational design of multi-component metal oxides by introducing cations into the structure according to simple criteria based on the redox potentials of different cations; rationally incorporating cations into metal oxide microparticles in a sequential manner; sequentially introducing up to six cations into the microparticles (~10 µm) according to the order of their redox potentials in aqueous solution at room temperature; cations that are already at the highest valence can also be added by activating the microparticles using reducing or intermediate valence ions;
[0017] (2) The present invention also develops a method for causing the highest valence cation to directly react with the superstructure material, and promotes the transformation of the superstructure material into a structure containing the highest valence cation. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 Schematic diagram of the cascade electroexchange reaction process;
[0019] Figure 2 Schematic diagram of the conformal transformation process from the first generation of Ag7O8NO3 superstructure material to the second generation of hollow AgNiO2 superstructure material and the crystal structure diagrams of Ag7O8NO3 and AgNiO2;
[0020] Figure 3 Preparation and characterization of Ag7O8NO3 superstructure materials, Figure 3 (A) is the potential waveform diagram for anodic electrodeposition of Ag7O8NO3 superstructure material; Figure 3 (B) is a scanning electron microscope (SEM) image of a structurally uniform Ag7O8NO3 superstructure material selectively peeled off from the electrode surface; Figure 3 (C) in the figure is the X-ray diffraction (XRD) pattern of Ag7O8NO3 superstructure material;
[0021] Figure 4 The SEM image and element mapping of AgNiO2 superstructure material; Figure 4 (A) is the SEM image of the AgNiO2 superstructure material; Figure 4 (B) in the figure is the Ag element mapping; Figure 4 (C) in the figure is Ni element mapping;
[0022] Figure 5 It is the energy dispersive X-ray spectrum (EDS spectrum), XRD spectrum and X-ray photoelectron spectrum (XPS spectrum) of AgNiO2 superstructure material; among them, Figure 5 (A) is the EDS spectrum of AgNiO2 superstructure material; Figure 5 (B) is the XRD spectrum of AgNiO2 superstructure material; Figure 5 (C) is the XPS spectrum of AgNiO2 superstructure material;
[0023] Figure 6 Schematic diagram of conformal transformation from AgNiO2 superstructure material to AgCoO2 superstructure material;
[0024] Figure 7 The SEM images and elemental mapping results of the second-generation AgNiO2 superstructure material, the third-generation Ag (Ni, Co) O2 superstructure material, and the AgCoO2 superstructure material after the cascade current displacement (CGD) reaction and the complete zinc displacement (GD) reaction; among them, Figure 7 (A) is the SEM image of the second-generation AgNiO2 superstructure material; Figure 7 (B) is the Ag element mapping result of the second-generation AgNiO2 superstructure material (2μm); Figure 7 (C) is the Ni element mapping result of the second-generation AgNiO2 superstructure material (2μm); Figure 7 (D) is the Ni element mapping result of the second-generation AgNiO2 superstructure material (4μm); Figure 7(E) is the SEM image of the CGD reaction of the third-generation Ag (Ni, Co) O2 superstructure material; Figure 7 (F) is the Ag element mapping result of the CGD reaction of the third-generation Ag (Ni, Co) O2 superstructure material (2μm); Figure 7 (G) in the figure is the Ni element mapping result of the CGD reaction of the third-generation Ag(Ni,Co)O2 superstructure material (2μm); Figure 7 (H) in the figure is the Co element mapping result of the CGD reaction of the third-generation Ag(Ni,Co)O2 superstructure material (2μm); Figure 7 (I) is the SEM image of the AgCoO2 superstructure material after complete GD reaction; Figure 7 (J) in the figure is the Ag element mapping result of the AgCoO2 superstructure material after complete GD reaction (2μm); Figure 7 (K) in the figure is the Co element mapping result of the AgCoO2 superstructure material after complete GD reaction (2μm); Figure 7 (L) in the middle is the Co element mapping result of the AgCoO2 superstructure material after complete GD reaction (3μm);
[0025] Figure 8 This is the XPS spectrum of AgCoO2 micro-torpedo;
[0026] Fig. 9 XRD spectra of AgNiO2 and AgCoO2 superstructure materials;
[0027] Fig.10 To monitor Co 3+ Ion pair Ni 3+ XPS spectra obtained from the displacement of ions;
[0028] Fig.11 Schematic diagram of preparing the fourth, fifth and sixth generation superstructure materials by cascade electrical exchange reaction; wherein, Fig.11 (A) is a schematic diagram of the oxidation potentials of different cations referenced in Example 2; Fig.11 (B) is the transmission electron microscopy (TEM) image and elemental mapping of the fourth-generation hollow Ag(Ni, Co, Mn)O2 superstructure material; Fig.11 (C) is the SEM image and elemental mapping of the fourth-generation hollow Ag (Ni, Co, Mn) O2 superstructure material; Fig.11 (D) in the figure is the EDS spectra of Ag(Ni, Co)O2 and Ag(Ni, Co, Mn)O2 superstructure materials; Fig.11 (E) is the SEM image and elemental mapping of the fourth-generation Ag (Ni, Co, Mn, Fe) O2 superstructure material; Fig.11(F) in the figure shows the SEM image and elemental mapping of the fifth-generation Ag (Ni, Co, Mn, Cr) O2 superstructure material; Fig.11 (G) in the figure is the XPS spectra of Ag(Ni, Co, Mn, Fe)O2 and Ag(Ni, Co, Mn, Cr)O2 superstructure materials; Fig.11 (H) is the SEM image and elemental mapping of the sixth generation Ag (Ni, Co, Mn, Cr, Fe) O2 superstructure material in Example 2;
[0029] Fig.12 The SEM image, EDS elemental image and XRD image of PbO2 converted from Ag7O8NO3 superstructure material; Fig.12 (A) is the SEM image and crystal structure of PbO2; Fig.12 (B) is the EDS element map of PbO2; Fig.12 (C) in the figure is the XRD pattern of PbO2;
[0030] Fig.13 The SEM image, EDS elemental image and XRD image of Fe2O3 converted from Ag7O8NO3 superstructure material; Fig.13 (A) is the SEM image and crystal structure of Fe2O3; Fig.13 (B) is the EDS element diagram of Fe2O3; Fig.13 (C) in the figure is the XRD pattern of Fe2O3;
[0031] Fig.14 The SEM image, EDS elemental image and XRD image of Ag converted from Ag7O8NO3 superstructure material; Fig.14 (A) is the SEM image and crystal structure of Ag; Fig.14 (B) is the EDS element map of Ag; Fig.14 (C) in the figure is the XRD pattern of Ag;
[0032] Fig.15 The SEM image, EDS elemental image and XRD image of Ag2S converted from Ag7O8NO3 superstructure material; Fig.15 (A) is the SEM image and crystal structure of Ag2S; Fig.15 (B) is the EDS element map of Ag2S; Fig.15 (C) in the figure is the XRD pattern of Ag2S;
[0033] Fig.16 The SEM image, EDS elemental image and XRD image of AgCl converted from Ag7O8NO3 superstructure material; Fig.16 (A) is the SEM image and crystal structure of AgCl; Fig.16 (B) is the EDS element map of AgCl; Fig.16 (C) in the figure is the XRD pattern of AgCl;
[0034] Fig.17 The SEM image, EDS elemental image and XRD image of AgI converted from Ag7O8NO3 superstructure material; Fig.17 (A) is the SEM image and crystal structure of AgI; Fig.17 (B) is the EDS element map of AgI; Fig.17 (C) in the figure is the XRD pattern of AgI;
[0035] Fig.18 The performance diagram of the controllable mobile Ag(Fe,Co)O2 magnetic superstructure material is shown in Figure 1. Fig.18 (A) is a schematic diagram of controlling the direction of the superstructure material without magnets and with moving magnets; Fig.18 (B) is a schematic diagram of controlling the direction of the superstructure material using magnets moving left and right respectively. DETAILED DESCRIPTION
[0036] The present invention is further described below in conjunction with specific embodiments, application examples and drawings of the specification. The methods in the embodiments are conventional methods and conditions unless otherwise specified.
[0037] The present invention uses a material with a high oxidation potential as a template to undergo an ion exchange reaction with a metal salt solution with a low oxidation potential, thereby achieving not only component conversion, but also the preparation of a multi-element high entropy alloy. The driving force for the chemical conversion is the standard reduction potential difference of the material. The metal salt solution with a low oxidation potential contains metal cations (such as Mn) in a relatively low valence state or an intermediate valence state. 2+ Cr 3+ , Fe 2+ The superstructure material with high oxidation potential should contain cations with strong oxidation ability and mobility, and can oxidize most of the intermediate cations.
[0038] Ag7O8 nitrate superstructure tends to react with metal cations with low oxidation potential. After reacting with metal cations with low oxidation potential, it cannot react with metal cations with higher oxidation potential than the former to form composite metal materials. 2+ The oxidation potential is 1.92 V, Ni 2+ 、Ni 3+ The oxidation potential is 1.977 V. When the AgNiO2 superstructure material is immersed in Co 2+ Ionic solution, Ni 3+ Reduce, Co 3+ Gradually replace Co 2+AgNiO2 and AgCoO2 have the same crystal structure. 3+ and Co 3+ The ionic radii of the Ag7O8 nitrate are similar, allowing the shape to be maintained during the process. The hollow AgNiO2 superstructure material gradually transforms into the third generation Ag(Ni,Co)O2 superstructure material, and finally transforms into AgCoO2 after the reaction is completed. Using this principle, the present invention demonstrates the introduction of up to 5 cations into the microstructure of Ag7O8 nitrate. According to the oxidation potential of the cations, according to Ni 3+ 、Co 3+ , Mn 3+ Cr 6+ and Fe 3+ The Ag7O8 nitrate superstructure material is introduced in the order of. Finally, the present invention realizes the manufacture of the sixth generation of Ag (Ni, Co, Mn, Cr, Fe) O2 superstructure material.
[0039] The materials prepared by the present invention have broad application prospects. For example, the hollow magnetic superstructures produced by this technology can be used as microcapsules to deliver drugs to required locations in the human body. The silver superstructures have wide applications in the analytical and biomedical fields as SERS substrates. Different cations can be identified based on the morphology of the converted structure of the Ag7O8 nitrate superstructure.
[0040] like Figure 1 As shown, it is a schematic diagram of the cascade electroexchange reaction process of the present invention; the process includes strong oxidizing cations (such as Ag in the first step) 2+ 、Ag 3+ and M in the second step 3+ ) and the dissolution of intermediate ions (such as M in the first step 2+ and N in the second step 2+ ) oxidizing cations (such as M in the first step) 3+ and N in the second step 3+ ) precipitation.
[0041] Example 1: Metal Ni is combined with Ag7O8NO3 superstructure material to form the first generation superstructure material.
[0042] The Ag7O8 nitrate superstructure material is produced by three gradually decreasing potential waveforms, which is a columnar structure. The front and rear ends of the columnar structure have a sharp end and a thick end. The surface of the columnar structure has indentations distributed symmetrically in the center, and the whole structure is streamlined, such as Figure 3 The preparation and characterization of Ag7O8NO3 superstructure materials are shown. By inserting the electrode into water, the uniformly electrodeposited Ag7O8 nitrate superstructure material is selectively stripped from the electrode surface. High-valent silver ions can remove Ni 2+ Oxidized to Ni 3 +(Oxidation potential: 1.977 V). The Ag7O8 nitrate superstructure material was introduced into the Ni 2+ In aqueous solution, Ag 3+ 、Ag 2+ From Ni 2+ Separate electrons to generate Ni 3+ In other words, the independent Ag7O8 nitrate superstructure material is used as a positive electrode to form a conductive electrode, and the Ni 2+ ions act as negative electrodes. High-valent silver ions gradually diffuse from the Ag7O8 nitrate core structure, and Ni 3+ 、Ni 2+ The ions gradually attach to the surface of the Ag7O8 nitrate superstructure material, forming a growing AgNiO2 shell, such as Figure 2 As shown. The crystallographic similarity between orthorhombic Ag7O8 nitrate and trigonal AgNiO2 reduces the lattice distortion between the Ag7O8NO3 and AgNiO2 shells. Figure 4~Figure 5 Shown are the SEM images, elemental mapping, and EDS, XRD, and XPS spectra of the AgNiO2 superstructure material.
[0043] Example 2: Introducing up to 5 cations into the Ag7O8 nitrate superstructure material.
[0044] According to the oxidation potential of the cation Fig.11 As shown in (A), according to Ni 3+ 、Co 3+ , Mn 3+ Cr 6+ and Fe 3+ The first generation of Ag7O8 nitrate superstructure material is successively converted into the second generation superstructure material AgNiO2, the third generation superstructure material Ag(Ni, Co)O2, the fourth generation superstructure material Ag(Ni, Co, Mn)O2, the fifth generation Ag(Ni, Co, Mn, Cr)O2 or Ag(Ni, Co, Mn, Fe)O2, and finally into the sixth generation superstructure material Ag(Ni, Co, Mn, Cr, Fe)O2. 2+ The cascade electrical exchange process between ions has obtained the fourth generation of hollow Ag(Ni, Co, Mn)O2 superstructure materials, such as Fig.11 Similarly, the fifth generation of hollow Ag(Ni, Co, Mn, Fe)O2 and Ag(Ni, Co, Mn, Cr)O2 superstructure materials were prepared, such as Fig.11 Finally, the present invention realizes the manufacture of the sixth generation Ag (Ni, Co, Mn, Cr, Fe) O2 superstructure material, as shown in (E) to (G) in FIG. Fig.11 As shown in (H) in the figure.
[0045] Take the preparation of the third-generation superstructure material Ag (Ni, Co) O2 as an example. Figure 6 The figure shows the conformal transformation from AgNiO2 superstructure material to AgCoO2 superstructure material. Figure 9~Figure 10 Shown are the XRD spectra of AgNiO2 and AgCoO2 superstructure materials, and the XPS spectroscopy monitoring of Co 3+ Ion pair Ni 3+ The result obtained by the displacement of ions; Figure 7 (A) to (L) in the figure respectively show the SEM images and element mapping results of the AgNiO2 superstructure material, the intermediate product Ag(Ni,Co)O2 superstructure material, and the AgCoO2 superstructure material. Among them, the open circuit voltage is used for detection. When the voltage is stable, it means that Co has completely replaced Ni to form AgCoO2. In this embodiment, the complete conversion from the AgNiO2 superstructure material to the AgCoO2 superstructure material is completed within 30 minutes. Therefore, the Ag(Ni,Co)O2 superstructure material is the product when the voltage is not stable. In each ion exchange reaction, the progress of the ion exchange reaction is detected by the open circuit voltage, and the reactants are separated before the open circuit voltage value is stable (that is, the nth generation superstructure material obtained by the reaction is taken out from the solution).
[0046] Example 3: A method for causing the highest valence cation to directly react with a superstructure material.
[0047] The present invention develops a method for causing the highest valence cation to directly react with the superstructure material, and promotes the transformation of the superstructure material into a structure containing the highest valence cation. A cation solution of intermediate valence is placed in a container, and an Ag7O8 nitrate microstructure is placed in a cation solution of the highest valence in another container. A copper wire is used to connect the carbon rod immersed in the first container to the gold electrode covered with the Ag7O8 nitrate microstructure. The two containers are connected to a liquid bridge, which is separated by a membrane and only allows nitrate ions to pass through. Co 2+ As the intermediate ion, Cu 2+ or Zn 2+ As its highest cation. Ultimately, the Ag7O8 nitrate microstructure is transformed into copper oxide and zinc oxide microstructure.
[0048] More importantly, this setup can also introduce its highest valent cations into the microstructure. For example, Zn 2+ ions have been successfully introduced into Ag(Ni, Co, Mn, Cr, Fe)O2 superstructure materials. For example, the elements of the intermediate valence ions can be replaced by reducing elements. 3+Applying a reduction potential to the Ag7O8 nitrate superstructure material in aqueous solution forms Fe2O3. The Ag7O8NO3 superstructure material can also be converted into metal oxides, metallic silver, silver sulfide and silver halide, such as Figure 12~Figure 17 Shown are the crystal structures, SEM images, EDS elemental images, and XRD images of PbO2, Fe2O3, Ag, Ag2S, AgCl, and AgI.
[0049] Application Example 1: Using hollow magnetic superstructures as microcapsules to deliver drugs in the human body.
[0050] The present invention further attempts to combine Ag7O8 nitrate superstructure material with Co 2+ and Fe 2+ The cascade electrical exchange reaction between the Ag7O8 nitrate superstructure material is converted into a hollow Ag(Co,Fe)O2 magnetic superstructure material. The hollow Ag(Co,Fe)O2 magnetic superstructure material responds to the magnetic field. The magnetic superstructure material can move quickly under the attraction of the magnet and can adjust the movement direction immediately. Fig.18 As shown in (A) to (B), from the direction from I to II, III and V of the Ag(Fe, Co)O2 superstructure material, it can be seen that the Ag(Fe, Co)O2 magnetic superstructure material can respond to the movement of the magnet.
[0051] These hollow magnetic superstructures have potential applications as microcapsules to deliver drugs where needed in the human body.
[0052] Application Example 2: Porous silver superstructures are widely used as SERS substrates in analytical and biomedical fields.
[0053] Nanoporous silver superstructure materials converted from Ag7O8 nitrate by electrochemical reduction can be used as surface enhanced Raman scattering (SERS) sensing substrates. The size of the nanopores in the silver superstructure materials can be controlled by the reduction potential. The Ag superstructure materials prepared under 3V electroreduction conditions showed outstanding SERS performance. These nanopores can significantly enhance the electromagnetic field and behave as SERS hotspots. Strong SERS peaks were observed for crystal violet (CV) molecules from their aqueous solutions at concentrations from 10 µm to 100.0 fm. These porous silver superstructure materials have a wide range of applications in analytical and biomedical fields as SERS substrates.
[0054] Application Example 3: Identification of different cations based on the morphology of the transition structure of Ag7O8 nitrate superstructure materials.
[0055] Ag7O8 nitrate superstructures can be used to detect intermediate ions. After 24 hours, a drop of liquid mixed with Ag7O8NO3 dried on a smooth surface to form nanorods and nanoparticles. In contrast, even in the presence of 1µm Mn 2+ 、Co 2+ or Ni 2 + The transformation structure morphology of the Ag7O8 nitrate superstructure material also undergoes significant changes. According to the transformation structure morphology of the Ag7O8 nitrate superstructure material, different cations can be identified.
[0056] It should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Without making creative work, any modification, equivalent replacement, improvement, etc., shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a high entropy alloy using cascade electrical exchange technology, characterized in that: The following steps are involved: Using (Ag7O8)X superstructure material as a template, ion exchange reactions are sequentially carried out with various metal salt solutions; in each ion exchange reaction, the progress of the ion exchange reaction is detected by open circuit voltage, and the reactants are separated before the open circuit voltage value stabilizes, thereby preparing a multi-component high entropy alloy hollow superstructure material; The oxidation potential of the metal cations in the plurality of metal salt solutions is lower than the oxidation potential of the silver ions in the (Ag7O8)X superstructure material, and the oxidation potential gradually decreases in the order in which the (Ag7O8)X superstructure material is introduced; the X anion is selected from NO3 - , HSO4 - , ClO4 - , F - , BF4 - One or more of; The (Ag7O8)X superstructure material is used as a template to sequentially undergo ion exchange reactions with a variety of metal salt solutions, specifically: the (Ag7O8)X superstructure material is used as a conductive electrode, a metal cation solution is used as an electrolyte, and a carbon rod is used as a counter electrode; high-valent silver ions gradually diffuse from the (Ag7O8)X superstructure material from the inside to the outside, and metal cations gradually adhere to the surface of the (Ag7O8)X superstructure material to form a growing AgYO2 shell, thereby obtaining a second-generation hollow metal oxide material AgYO2, wherein Y is a metal element in the metal cation; the second-generation hollow metal oxide material AgYO2 is used as a template, and the above steps are repeated to react with metal cations with an oxidation potential lower than Y to obtain a multi-generation multi-component high-entropy alloy hollow superstructure material.
2. The method according to claim 1, characterized in that: The concentration of the metal salt solution is greater than 50 mmol / L.
3. The method according to claim 1, characterized in that The (Ag7O8)X superstructure material is prepared by the following method: a three-electrode system is used, a deionized water solution containing a silver ion compound and H3BO3 is used as an electrolyte, and a step-by-step decreasing voltage mode or a multiple step-by-step decreasing voltage mode is used to electro-deposit the (Ag7O8)X superstructure material on a working electrode; wherein the voltage of the electro-deposition is greater than or equal to 1.5 V, and the silver ion compound is one or more of AgNO3, Ag2SO4, AgClO4, AgF, and AgBF4.
4. The method according to claim 1, characterized in that: Also includes: The highest valence cation is introduced into the (Ag7O8)X superstructure material or the nth generation multi-component high entropy alloy hollow superstructure material, specifically, the intermediate valence cation solution is placed in a first container, a carbon rod is inserted, the highest valence cation solution to be introduced is placed in a second container, a gold electrode covered by the (Ag7O8)X superstructure material or the nth generation multi-component high entropy alloy hollow superstructure material is inserted, the gold electrode is connected to the carbon rod by a copper wire, the first container and the second container are connected by a liquid bridge, an ion exchange membrane is arranged in the liquid bridge, and only X anions are allowed to pass; wherein the oxidation potential of the intermediate valence cation is higher than that of the highest valence cation.